Penundaan Pembagian Harta Waris Pasca Kematian Orang Tua - Badi’, Ahmad; Iqbal, Moh. (JOM, 2024)
Inheritance is a law that regulates the transfer of assets inherited from people who have died and also the rights of heirs. It should be noted that the process of distributing inheritance assets should be immediately distributed to the heirs, but what is happening in the Semen Village community is the opposite, many of them are delaying the distribution of inheritance assets, which is far from the existing provisions.The research method used is a qualitative method, with this method it is much easier for researchers to produce descriptive data, namely trying to understand and comprehend an event and problem that occurred, where research data is taken from notes, books, journals, interviews and other literature. The delay in distributing inheritance in the Semen Village community is caused by several factors, including: 1) one of the parents of the heir is still alive 2) the tradition of waiting 40 to 100 days after the death of the parent 3) one of the heirs is still outside City 4) there was a dispute regarding the share obtained by each heir. As for the postponement of the distribution of inheritance that has occurred in Semen Village, so far it is not in conflict with the Shari'a, although there are still some families who do not comply with the method of distribution, the majority of the people of Semen Village have complied with the existing provisions due to several reasons for the delays that have occurred in the Village. This cement is a reason that is legalized by the Shari'a.